Analisis Pengembangan Wisata Golden Prawn Dan Pengaruh Peningkatannya Terhadap Konservasi Lingkungan Dan Keberlanjutan Di Kepulauan Riau - Azali, Dara Larasati; Sulistiana, Vina (Institut Seni Indonesia Padangpanjang, 2023)
Tourism in the Riau Islands is rapidly growing, with Golden Prawn as a major destination attracting many visitors. This research aims to analyze the development of Golden Prawn tourism and its impact on environmental conservation and sustainability in the region. The research method used is qualitative, descriptive, and analysis 3A with data collection through interviews, field observations, and literature review.The results show that Golden Prawn has experienced a significant increase in visits in recent years. Further development potential is evident from market demand and the natural potential in its surroundings. However, this development also brings environmental impacts, such as ecosystem degradation and increased waste.In the context of sustainability, the contribution of Golden Prawn to the local economy and cultural preservation is crucial. However, further efforts are needed to mitigate negative environmental impacts. This research provides recommendations for tourism managers and local governments to integrate sustainability principles into the development and management of Golden Prawn.